Effect of Peptide Drug Liraglutide Nano-Formulation Combined with Sodium-Glucose Cotransporter-2 Inhibitor on Blood Lipids in Patients with Type 2 Diabetes: Peptide Drug Liraglutide Nano-Formulation and Type 2 Diabetes - She, Yuqing; Liu, Zelong (Cellular and Molecular Biology, 2022)
With the aging of our population and the increase in the number of obese people, diabetes has become a common disease. At present, drug treatment is mainly used for diabetes. Dyslipidemia is the main cause of diabetes. The regulation of blood lipids in diabetic patients through drugs is the key to treating diabetes. The purpose of this article is to further explore the specific effect and mechanism of peptide drug liraglutide nano-formulation combined with sodium-glucose co-transporter-2(SGCT-2) inhibitor on blood lipids in patients with type 2 diabetes. This article uses 30 people included in our hospital in 2019 2 patients with type 2 diabetes are divided into the group of peptide drug liraglutide nano preparations, the group of SGCT-2 inhibitors and the peptide drug liraglutide nano preparations combined with SGCT-2. In the inhibitor combination medication group, patients were given drug intervention according to the group name with the consent of the patients. After three days, the serum cholesterol, triglyceride, lipoprotein and lipid metabolism levels of all patients were tested. The results showed that under the intervention of peptide drug liraglutide nanoparticles combined with SGCT-2 inhibitor, the cholesterol level of patients with type 2 diabetes decreased from (368.2 ± 8.3) mmol / L to (1978.4 ± 4.7) mmol/L, triglyceride level decreased from (653.7 ± 12.5) mg/dL to (426.8 ± 9.6) mg/dl, and lipid metabolism level increased by 25.6%. Therefore, it can be seen that the peptide drug liraglutide nano preparation combined with SGCT-2 inhibitor has a certain therapeutic effect on type 2 diabetes.